Selectively capacitive recovery of rare earth elements from aqueous solution onto Lewis base sites of pyrrolic-N doped activated carbon electrodes. (September 2022) - Zhao, Feiping; Chen, Shixing; Xiang, Hongrui; Gao, Tianyu; Wang, Danyang; Wei, Dun; Sillanpää, Mika; Ke, Yong; Tang, Chong-Jian
Abstract: The growing demand for rare earth elements (REEs) necessitates cheap and environmentally friendly technologies for REEs recovery. Herein, we fabricated a pyrrolic-N doped activated carbon electrode (PPyN-AC) via two facile steps of in-situ polymerization of pyrrole monomers and further carbonization. Capacitive deionization (CDI) using PPyN-AC as electrodes is the first time applied for REEs capture from aqueous solution. PPyN-AC possesses a high N doping rate (9.55 at.%) and excellent capacitance (128.98 F/g). The CDI flow-by tests shows that the electrosorption capacity of La(III) by PPyN-AC electrode was 23.66 mg/g within 25 min at optimal conditions. The rapid and efficient La(III) electrosorption performance is attributed to the pyrrole-N configuration in the carbon matrix. Beyond that, the PPyN-AC electrode could selectively capture La(III) from a quaternary-component system of La(III), Fe(III), Ca(II) and Na(I) in aqueous solution. The REE selectivity mechanism, which involves the ionic charge, hydrated radii of metal ions, and hard-soft Lewis acid-base principle, was proposed. Overall, this work demonstrates a new efficient approach for the selective recovery of REEs from aqueous solution with minimal land and energy demands. Graphical abstract: The study reported a straight route to prepare pyrrolic-N doped AC serving as capacitive deionization electrode for the recovery of REEs from wastewater. The proposed PPyN-AC electrode exhibits excellent selectivity toward La(III) in the presence of competitive ions. Image 1 Highlights: Capacitive deionization (CDI) system for REEs recovery is first proposed. CDI realized 23.66 mg/g La(III) uptake within 25 min by PPyN-AC electrode. PPyN-AC selectively electrosorbed La(III) from a mixture of La–Fe–Ca–Na. The pyrrole-N configuration contributes in the selective capture of REEs.